The Effect of Husband Support and Economic Status Level on Exclusive Breastfeeding - Maria Oktaviana Mamoh; Gunarmi Gunarmi; Juda Julia Kristiarini (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
The main problem of low exclusive breastfeeding in Indonesia is the influence of socio-cultural factors and lack of knowledge of pregnant women, families, and communities. This study aims to determine the effect of husband support and economic status level on exclusive breastfeeding. This research is quantitative with a cross-sectional approach where this design emphasizes the time of data measurement and observation of both variables. The sample of this study amounted to 57 respondents. The results of the study found that H1 received showed the influence of husband support on exclusive breastfeeding, H2 received showed the power of the level of economic status on exclusive breastfeeding, H3 received husband support and the level of financial quality simultaneously or jointly affected the dependent variable, namely exclusive breastfeeding. It can be concluded that husband support has a natural effect on partial exclusive breastfeeding, the influence of the level of economic status on exclusive breastfeeding, and husband support and the level of financial quality affect exclusive breastfeeding